Development of Plant Biosystematics E-Module Based on Problem Solving - Sekar Jati Pamungkas; Wike Oktasari (Indonesian Journal of Biology Education, 2020)
This study aims to describe the stages of developing the Plant Biosystematics e-module with the 4-D model (four D model) and to analyze the effectiveness of the resulting Plant Biosystematics e-module in improving problem solving skills in students of the Tidar University Biology Education Study Program. The Plant Biosystematics course studies the description, adaptation, and classification of plants, both high and low levels. The research method used is the R&D Model. This model consists of 4 development stages, namely Define, Design, Develop, and Disseminate. The object of this research was 60 students of Tidar University Biology Education. The research instrument used was in the form of questionnaires and validation sheets by the validator. Based on data on Problem Solving skills 38, 3% chose the number 5 meaning that in this Plant Biosystematics e-module all 5 indicators have been fulfilled. Based on the development of the e-module by the validator, the results of the material were 80.5%, the presentation aspect was 54%, the linguistic aspect was 24%, and the graphic aspect was 34%. Based on the data above, the development of the Plant Biosystematics e-module can be used as a learning module that can improve their problem solving skills.